Assessment of Nutritional Status for Nutritional Rickets Identification in Children Less Than Five Years of Age - Muhammad Amir, Imran Ahmad, Ghulam Shabir Laghari, Hafiz Abdul Quddus, Muhammad Sajjad Sabir, Masood Murad Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To estimate the nutritional status for nutritional rickets identification in children <5 years of age. Study design: Prospective study Place and duration of study: Memon Hospital Hyderabad from 1st February 2022 to 31st January 2023. Methodology: One hundred children under the age of 5 were enrolled. Nutritional rickets diagnosis was based on clinical and biochemical examination followed by radiological imaging. The radiological X-ray was used for identifying spraying, fraying, cupping and widening of wrist presence. A 2cc blood of each patient was withdrawn and test for the levels of 25(OH) vitamin D3, serum calcium and alkaline phosphatase (ALP) through Enzyme linked immune sorbent assay and calorimetric method respectively. For each patient a food frequency chart was fulfilled which included their breast feeding, supplementation, cerelac and cow milk diet intake as well as intake of other dairy products. Results: Radiological assessment of present study showed that cupping was the most prominent determinant followed by wrist widening and splaying in all age groups. In present study, rural participants are more exposed to sun light as compared to urban participants. Biochemical analysis revealed that means calcium, ALP and vitamin D levels was lower in almost every age group. Food frequency chart proved, 66% of the children were on breastfeeding but only 34% of the patients were taking supplements along with breastfeeding. Practical Implication: supplementation and adequate awareness are the key elements that can prove substantial in improving the vitamin D status in developing regions of the world. Conclusion: Majority of the children of present study were vitamin D and calcium deficient. Keywords: Rickets, Vitamin D, Calcium, Sunlight